2017
DOI: 10.3389/fmicb.2016.02121
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of “Candidatus Accumulibacter Phosphatis” Clade II C to Changes in Influent P/C Ratio

Abstract: The objective of this study was to investigate the ability of a culture highly enriched with the polyphosphate-accumulating organism, “Candidatus Accumulibacter phosphatis” clade IIC, to adjust their metabolism to different phosphate availabilities. For this purpose the biomass was cultivated in a sequencing batch reactor with acetate and exposed to different phosphate/carbon influent ratios during six experimental phases. Activity tests were conducted to determine the anaerobic kinetic and stoichiometric para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Accumulibacter subclades switched from IA to IIA. Previously, Acevedo et al (2012) and Welles et al (2015, 2017) showed that both clades of Ca . Accumulibacter could solely rely on glycogen for the generation of ATP and NADH under phosphate limiting conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Accumulibacter subclades switched from IA to IIA. Previously, Acevedo et al (2012) and Welles et al (2015, 2017) showed that both clades of Ca . Accumulibacter could solely rely on glycogen for the generation of ATP and NADH under phosphate limiting conditions.…”
Section: Discussionmentioning
confidence: 94%
“…For both cultures, anaerobic P-release per C-fed indicated that the PAO present in the sludge are likely saturated with polyphosphate and that glycogen accumulating organisms (GAO) are not present (37). Furthermore, microbial characterization by FISH showed Accumulibacter from clade I were the majority of the microorganisms across all biomass samples as it can be seen by the high overlap between the Accumulibacter-specific probe and the general Bacteria probe (micrographs available in Supplementary Document S3).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments show that the ratio between glycogen and acetate consumption by PAOs is variable, e.g. between high/low temperature (42) or polyphosphate/glycogen availability (37, 43, 44). To reflect this variability, simulations were performed for a range of acetate and glycogen mixtures ranging from only acetate to only glycogen and results were compared to experimental data reported in literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported PAOs mainly affiliated with the Rhodocyclus group of the Betaproteobacteria, which were named "Candidatus Accumulibacter phosphatis" (6). From laboratory-scale to full-scale EBPR systems, "Candidatus Accumulibacter" was a numerically dominant PAO (7,8). Real-time quantitative PCR (qPCR) and fluorescence in situ hybridization (FISH) are the primary approaches for quantitative analysis of PAOs.…”
mentioning
confidence: 99%